Online travel agencies: factors influencing tourists’ purchase decisions - Ivete Pinto; Conceição Castro (Tourism & Management Studies)
This study sought to analyse tourists’ purchasing behaviours involving online travel agencies (OTAs) (i.e. Booking.com and Expedia.com). The research focused on identifying which factors most strongly influence buyers’ decision making and whether the degree of importance given to factors changes according to tourists’ sociodemographic, economic or travel characteristics. The results show that most tourists book their accommodations through OTAs mainly because browsing is easier and better prices are offered. The results further suggest that the most important factor when booking accommodations is price, although the overall buying process is quite complex. Online reviews, promotions and photos are also important. The importance online tourists give to price varies by age group, income and country of residence. Online reviews are significant regardless of tourists’ characteristics, except for age. Cluster analyses additionally revealed three different tourist segments based on the importance given to price, online reviews, promotions and photos